1993
DOI: 10.1016/0014-5793(93)80522-v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pteridine derivatives on intracellular calcium concentration in human monocytic cells

Abstract: Pteridines are heterocyclic compounds which are synthesized and released by human monocytes/macrophages following stimulation by interferonγ. Their concentration in various body fluids proved to be indicative for the stimulation of the cellular immune system, and determination of pteridines has become an important diagnostic tool. We show that pteridine derivatives, namely neopterin (N), 7,8‐dihydroneopterin (NH2), and 5,6,7,8‐tetrahydrobiopterin (BH4) increase intracellular calcium (Cai) in human monocytic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 20 publications
2
9
1
Order By: Relevance
“…Elevation of the cytosol calcium concentration has also been considered to be an important factor for superoxide generation in phagocytes. Recently, it has been demonstrated that pteridine derivatives such as NP increase intracellular calcium concentration in human monocytes, and it was suggested that they are involved in the regulation of calcium-mediat-ed macrophage activation including superoxide generation [20]. Another important factor for the superoxide generation is protein kinase C (PKC).…”
Section: Resultsmentioning
confidence: 99%
“…Elevation of the cytosol calcium concentration has also been considered to be an important factor for superoxide generation in phagocytes. Recently, it has been demonstrated that pteridine derivatives such as NP increase intracellular calcium concentration in human monocytes, and it was suggested that they are involved in the regulation of calcium-mediat-ed macrophage activation including superoxide generation [20]. Another important factor for the superoxide generation is protein kinase C (PKC).…”
Section: Resultsmentioning
confidence: 99%
“…Schobersberger et al demonstrated that incubation of vascular smooth muscle cells (VSMCs) with neopterin promotes nitric oxide synthase gene expression and nitric oxide release (29). In addition, neopterin was found to increase intracellular Ca 2ϩ , indicating a direct role in the production of ROS and NO (37). Furthermore, neopterin was found to amplify the secretion of tumor necrosis factor alpha (TNF-␣) by peripheral blood mononuclear cells induced by lipopolysaccharide (LPS), IFN-␥, and interleukin-2 (4) and to stimulate TNF-␣ gene expression as well as TNF-␣ release and nuclear uptake of NF-B in VSMCs (16).…”
Section: Discussionmentioning
confidence: 97%
“…In THP-1 cells, neopterin was found to increase intracellular Ca 2+ concentrations, indicating a direct role in the production of reactive species [44]. In vitro-studies using cellfree solutions showed that neopterin enhances hydrogen peroxide-and chloramine-T-dependent chemiluminescence.…”
Section: Neopterin and Oxidative Stressmentioning
confidence: 99%